The pattern of herbal medicines use for breastfeeding mother in Jogonalan, Klaten, Indonesia: a mini survey - Nutrisia Aquariushinta Sayuti; Nur Atikah (BMC, 2023)
Abstract Background and objectives Indonesian society extensively uses herbal medicine due to its abundant natural resources that have been utilized for generations for health purposes. Herbal medicine is also employed by specific community groups, such as breastfeeding mothers, to address issues like low milk production. However, there has yet to be much research conducted on its usage patterns in the Jogonalan District, Klaten Regency, Indonesia. It is crucial to understand this aspect to gain an overview of herbal medicine utilization in the community, thus preserving local's healthy traditional culture and traditions and continuing their development. This study aims to describe the pattern of herbal medicine usage among breastfeeding mothers in the Jogonalan District, Klaten Regency, Central Java Province, Indonesia. Methods The quantitative descriptive study conducted as a mini survey to breastfeeding mothers who used herbs, visited minimal three (3) times in integrated service posts for babies/toddlers in the Jogonalan sub-district and agree to overcome the research. Calculating the frequency distribution was used to analyze the study's findings. The advantages and disadvantages of these results are evaluated in relation to the findings of earlier investigations. Results and conclusions The respondents were dominated housewives (84.4%), aged 20-35 years (71.1%), had secondary education (60.0%), and multiparous (66.7%). The daily use of uyub-uyub as a breast milk enhancer dominates the pattern of herbal medicine use. Papaya leaves, turmeric, and aromatic ginger are further herbal remedies. Nursing mothers' health and fitness and breastfed children's health is other advantages. The only adverse effects reported by three respondents (6.7%) were nausea and dizziness. Breastfeeding mothers can safely utilize evidence-based herbal medicines by increasing their knowledge, consulting with health professionals, and using them under supervision to preserve their use.